Method of associated treatment of upper limb lymphatic oedema in breast cancer patients after mastectomy - Renkielska, Alicja; Grobelny, Irena; Grudziński, Jacek; Jaśkiewicz, Janusz; Nyka, Wiesława (Contemporary Oncology/Współczesna Onkologia, 2003)
An annual figure of over 8000 women in Poland will undergo mastectomy for cancer and subsequently, some of them will be subjected to adjuvant radiotherapy. Despite conservative prophylaxis, 30% of those patients will develop a lymphatic oedema of the upper limb that will necessitate intensive rehabilitation or other forms of conservative treatment. Notwithstanding that treatment, 20% of the subjects will suffer from a permanent lymphatic oedema that will call for a surgical procedure. The aim of the paper was to develop our own method of associated treatment for permanent lymphatic oedema in mastectomy patients and to assess the early and late results of the therapy as well as to compare the effectiveness of the treatment instituted on the basis of the degree of the oedema subsiding. The study embraced a group of 36 patients coming from the two centres, the Department of Plastic Surgery and Treatment of Burns, Medical Univesity of Gdańsk (24 female subjects), and the Department of Breast Diseases and Reconstructive Surgery in Warsaw (12 female patients). The current paper was conceived to be of a prospective character. In 21 subjects, surgical treatment took the form of muscular-venous by-pass that consisted in transferring a peduncled flap of the latissimus dorsi muscle to the vicinity of the oedematous arm. In 18 subjects, the method was that of ultrasound liposuction with an apparatus of Sonoca &reg ; 400/ LIPO manufactured by Sóring. The two groups of the patients had comparable clinical characteristics. The paper presents and analyzes our own surgical techniques. The assessment of treatment results was done by showing the average value of oedema volume (the difference between the volume of the oedema-affected upper limb and the volume of the healthy limb), and the percentage reduction of the average oedema volume in the two groups under study. The material thus obtained was statistically analyzed. With all the research done in the current study, the two methods applied were found to be safe and well tolerated by the subjects. Following the ultrasound liposuction procedure, there was an effective and permanent diminishing of lymphatic oedema – the reduction in oedema was 83.7% one year after the operation, while after the muscular-venous by-pass procedure, the respective reduction was only 21.6%. The treatment of permanent lymphatic oedema that continues to be a serious problem Poland-wide, is a difficult, multi-discipline and time-consuming task and as such, should be done by specialists working as a team on combating the condition.